THE ARTICULATION OF ISLAMIC MULTICULTURAL EDUCATION OF DAYAH MUDI MESRA AL-AZIZIYAH NETWORK IN ACEH PEACE - Muhammad Riza; Maskuri; Mistar, Junaidi (The Islamic Education and Multiculturalism Foundation, 2022)
Dayah has a significant role in the socio-religious life of the Acehnese. One of the important roles that the dayah institution has played in recent decades is its role in bridging peace in Aceh. This study aims to explore the role of Dayah Mudi Mesra Al-Aziziyah Samalanga in articulating Islamic multicultural education in Aceh. This study uses a qualitative research approach with case study where the data sources are taken purposefully on 20 informants from Dayah Mudi Mesra Samalanga and figures involved in Aceh peace. Data were collected using in-depth interview and documentation techniques. The data obtained were then analyzed using interactive analytical model. The results show that the articulation of Islamic Multicultural Education of Dayah Mudi Mesra Al-Aziziyah Samalanga is carried out into two forms, they are 1) Internalization of values ​​through the Tastafi curriculum, 2) Externalization through involvement in peace in the conflict between GAM (Free Aceh Movement) and the Indonesian Central Government.